Short chain fatty acids: Microbial metabolites for gut-brain axis signalling - O'Riordan, Kenneth J.; Collins, Michael K.; Moloney, Gerard M.; Knox, Emily G.; Aburto, María R.; Fülling, Christine; Morley, Shane J.; Clarke, Gerard; Schellekens, Harriët; Cryan, John F. (Molecular and cellular endocrinology, 2022)
The role of the intestinal microbiota as a regulator of gut-brain axis signalling has risen to prominence in recent years. Understanding the relationship between the gut microbiota, the metabolites it produces, and the brain will be critical for the subsequent development of new therapeutic approaches, including the identification of novel psychobiotics. A key focus in this regard have been the short-chain fatty acids (SCFAs) produced by bacterial fermentation of dietary fibre, which include butyrate, acetate, and propionate. Ongoing research is focused on the entry of SCFAs into systemic circulation from the gut lumen, their migration to cerebral circulation and across the blood brain barrier, and their potential to exert acute and chronic effects on brain structure and function. This review aims to discuss our current mechanistic understanding of the direct and indirect influence that SCFAs have on brain function, behaviour and physiology, which will inform future microbiota-targeted interventions for brain disorders.